UPAYA PENGEMBANGAN DALAM STRATEGI INOVASI MENU DAN PENGEMBANGAN PRODUK UNGGULAN UMKM KULINER DI KOTA SERANG - Khaeruman, Khaeruman; Tabroni, Tabroni; Suflani, Suflani; Hanafiah, Hafidz; Bahits, Abdul; Kartika, Rika; Salapudin, Salapudin; Fatari, Fatari (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
This community service activity aims to support the development of menu innovation strategies and flagship product enhancement for culinary MSMEs in Serang City. The program focused on recipe innovation training, packaging improvements, and strengthening digital marketing. Five culinary MSMEs actively participated in this month-long activity conducted in January 2025. The methods included preliminary observation, direct training, and evaluation of implementation outcomes. Results showed that the training improved MSME actors’ creativity in producing new menu variations and enhancing product packaging. Furthermore, strengthening digital marketing significantly contributed to improving competitiveness and sales. Based on evaluations, all participating MSMEs showed progress in innovation, branding, and market reach. This program demonstrates that an integrated approach through direct training is highly effective in enhancing the capacity of culinary MSME entrepreneurs. In the future, collaboration between universities, government, and MSME communities should be expanded to support sustainable growth and innovation of local MSMEs.